Hip Taping Positively Alters Running Kinematics in Asymptomatic Females - Masters, Ashleigh; Netto, Kevin J.; Brooker, Susi; Hopper, Diana; Liew, Bernard (International Journal of Sports Medicine, 2018)
Greater functional knee valgus (FKV) is thought to contribute to a greater risk of sustaining overuse running injuries. The hip is commonly implicated in greater functional knee valgus, but no studies have investigated the effects of hip taping on running kinematics. The present study investigated whether or not hip taping altered hip and knee kinematics compared to sham and no taping in female runners demonstrating excessive functional knee valgus. Lower limb stance-phase kinematics were collected from 23 female runners using three-dimensional motion capture. Participants performed over ground running at 3.5 m/s and 5.0 m/s. Three taping conditions (no tape; sham tape; hip tape) were tested. Statistical inference was performed using Statistical Parametric Mapping Hotelling’s paired t-tests, with post-hoc paired t-tests. Hip taping significantly decreased hip adduction and internal rotation angles throughout stance phase by up to 7°, compared to sham and no taping. Hip taping significantly increased knee adduction, internal rotation, flexion, and reduced peak knee flexion angles, compared to no tape. Hip taping reduced excessive hip motion by clinically meaningful magnitudes, and also benefited knee frontal and transverse plane kinematics at the slower running speed. Hip taping may provide an immediate solution in correcting FKV in running.
Keywords: biomechanics; taping; overuse injuries; running; kinematics